Cupid’s quiver: Integrating sensory cues in rodent mating systems - Hoglen, Nerissa E. G.; Manoli, Devanand S. (Frontiers in Neural Circuits, 2022)
In many animal species, males and females exploit different mating strategies, display sex-typical behaviors, and use distinct systems to recognize ethologically relevant cues. Mate selection thus requires mutual recognition across diverse social interactions based on distinct sensory signals. These sex differences in courtship and mating behaviors correspond to differences in sensory systems and downstream neural substrates engaged to recognize and respond to courtship signals. In many rodents, males tend to rely heavily on volatile olfactory and pheromone cues, while females appear to be guided more by a combination of these chemosensory signals with acoustic cues in the form of ultrasonic vocalizations. The mechanisms by which chemical and acoustic cues are integrated to control behavior are understudied in mating but are known to be important in the control of maternal behaviors. Socially monogamous species constitute a behaviorally distinct group of rodents. In these species, anatomic differences between males and females outside the nervous system are less prominent than in species with nonmonogamous mating systems, and both sexes engage in more symmetric social behaviors and form attachments. Nevertheless, despite the apparent similarities in behaviors displayed by monogamous males and females, the circuitry supporting social, mating, and attachment behaviors in these species is increasingly thought to differ between the sexes. Sex differences in sensory modalities most important for mate recognition in across species are of particular interest and present a wealth of questions yet to be answered. Here, we discuss how distinct sensory cues may be integrated to drive social and attachment behaviors in rodents, and the differing roles of specific sensory systems in eliciting displays of behavior by females or males.